Partial validation of cellular automata based model simulations of urban growth: An approach to assessing factor influence using spatial methods. (July 2015) - Barreira González, Pablo; Aguilera-Benavente, Francisco; Gómez-Delgado, Montserrat
Abstract: Cellular Automata (CA) based models have a high aptitude to reproduce the characteristics of urban processes and are useful to explore future scenarios. However, validation of their results poses a major challenge due to the absence of real future data with which to compare them. A partial validation applied to a CA-based model for the Madrid Region (Spain) is presented as a proposal for determining the influence of given factors on the results and testing their spatial variability. Several simulations of the model were computed by different combinations of factors, and results were compared using flexible map comparison methods in order to study spatial pattern matches and similarities between them. Main and total effects of these factors were calculated for each method, by applying a simplified Global Sensitivity Analysis approach. Frequency maps showing the most frequent cells with changed land use in the results were generated. Highlights: A set of runs were computed for all possible combinations of main input factors. Generated simulations were compared using spatial metrics and buffer zones. The main and total effects of each parameter were computed for each method employed, applying a simplified GSA. A stability (frequency) map was made for the different simulations generated to detect the more robust areas. This simple methodology is an attempt to improve modeller-planner communication and understanding.